Liver perforation caused by modified biliary stent of nasobiliary duct：a case report - JIAO Yuanjun, YIN Yaoxin, LI Guixian, LIU Jikui, LIN Zewei (Waike lilun yu shijian)
There are many cases of biliary stent migration. Generally, biliary stent migrates distally. While, biliary stent rarely migrates proximally. Here we reported the case of a 49-year-old woman who underwent robot assisted right hemihepatectomy, and placement of a biliary stent for complicating bile leakage. The patient was discharged from hospital after recovering from bile leakage. Five months later, a follow-up examination revealed that the biliary stent had shifted into the liver, leading to liver perforation. We fully removed the stent by using a stone retrieval balloon and a snare. We suggested that when useing a biliary stent, it is necessary to consider of appropriate length of the stent and inform the patient when to return to the hospital for stent removal, in order to avoid stent migration and complications occurrence.